Masjid Friendly: Mosque Based Economic Empowerment - Lia Dwi Utami; Muhammad Amin; Mustafiyanti Mustafiyanti; Frances Alon (Pengabdian: Jurnal Abdimas, 2023)
Background. This research aims to offer a friendly mosque movement. The friendly mosque movement aims to make the mosque the main base in empowering the people's economy by referring to QS. at-Taubah (9): 18. Purpose. To examine this in this study, researchers used the type of library research (literature study), using primary and secondary sources, and using data analysis techniques which include data reduction, data presentation, and verification. Method. Of these four programs, it can be realized in the form of a friendly mosque movement that can be used as a foundation for the economic empowerment of the people. Results. The results of this study are the friendly mosque movement through three management instruments, namely: 'idarah (management); 'imarah (pemmukran); ri'ayah (maintenance and procurement of facilities), can realize four programs which include: 1) Eco-Masjid Program; 2) Independent Mosque Program; 3) Productive Mosque Program; 4) Child Friendly Mosque Program. Conclusion. If the idea of a friendly mosque with these four programs is applied to 290,161 mosques in Indonesia, then the economic problems of the people will be solved and the mosque will be the main instrument in solving these social problems.